LPS-induced NFκB enhanceosome requires TonEBP/NFAT5 without DNA binding - Lee, Hwan Hee; Sanada, Satoru; An, Seung Min; Ye, Byeong Jin; Lee, Jun Ho; Seo, Young-Kyo; Lee, Changwook; Lee-Kwon, Whaseon; Küper, Christoph; Neuhofer, Wolfgang; Choi, Soo Youn; Kwon, Hyug Moo (Scientific reports, 2016)
NFκB is a central mediator of inflammation. Present inhibitors of NFκB are mostly based on inhibition of essential machinery such as proteasome and protein kinases, or activation of nuclear receptors; as such, they are of limited therapeutic use due to severe toxicity. Here we report an LPS-induced NFκB enhanceosome in which TonEBP is required for the recruitment of p300. Increased expression of TonEBP enhances the NFκB activity and reduced TonEBP expression lowers it. Recombinant TonEBP molecules incapable of recruiting p300 do not stimulate NFκB. Myeloid-specific deletion of TonEBP results in milder inflammation and sepsis. We discover that a natural small molecule cerulenin specifically disrupts the enhanceosome without affecting the activation of NFκB itself. Cerulenin suppresses the pro-inflammatory activation of macrophages and sepsis without detectable toxicity. Thus, the NFκB enhanceosome offers a promising target for useful anti-inflammatory agents.